Multiple Micronutrient Deficiency Among Adolescent Girls with Normal Nutritional Status - Need for Fortified Nutritional Support in Rural Settings of South Tamil Nadu, India - K, Sunitha; Muthu G; Arockiasamy, Jesuraj; Maryam Jamila S; Yuvaraj J; Shantaraman K (National Journal of Community Medicine, 2024)
Introduction: Adolescents contribute to one fifth of the world's population and is a high priority lifecycle stage for nutrition needs and intervention. Nutritional deficiency, including micronutrients, hinders their normal growth and development. Improving adolescent girls’ nutrition has reproduction-related benefits and serves as a unique opportunity to break the vicious cycle of intergenerational structural problems. The objective is to estimate the prevalence of anaemia, micronutrient deficiency and nutritional status among adolescent girls in rural India. Methods: A community-based cross-sectional study was conducted among 241 adolescent girls in rural Tirunelveli, India with 220 blood samples. Results: The mean age of 241 adolescent girls was 13.8±1.4 years and nutritional status was normal, overweight, obese, thin and stunted in 81.7%, 14.5%, 3.3%,0.4% and 4.6% respectively. The prevalence of anaemia, iron deficiency and iron-deficiency anaemia were 37.2%, 34.5% and 12.3%. Except for selenium, the estimated micronutrient deficiency levels were Vitamin B12 - 40.9%, Copper-30.9%, Zinc-13.6% and Iodine- 11%. Only 19.1% girls had adequate levels of all micronutrients. Vitamin B12 deficiency was more in girls who were overweight (p<0.05). Conclusion: Multiple micronutrient deficiency with normal nutritional status is high among adolescent girls with Vitamin B12 deficiency higher than Iron. Multipronged strategies, including introducing micronutrient fortified healthy snacks in schools, might bring greater acceptance and improvement in nutritional health among these girls.